Mice Heterozygous for the Sodium Channel Scn8a (Nav1.6) Have Reduced Inflammatory Responses During EAE and Following LPS Challenge - Alrashdi, Barakat; Dawod, Bassel; Tacke, Sabine; Kuerten, Stefanie; Côté, Patrice D.; Marshall, Jean S. (Frontiers in Immunology, 2021)
Voltage gate sodium (Nav) channels contribute to axonal damage following demyelination in experimental autoimmune encephalomyelitis (EAE), a rodent model of multiple sclerosis (MS). The Nav1.6 isoform has been implicated as a primary contributor in this process. However, the role of Nav1.6 in immune processes, critical to the pathology of both MS and EAE, has not been extensively studied. EAE was induced with myelin oligodendrocyte (MOG35-55) peptide in Scn8admu/+ mice, which have reduced Nav1.6 levels. Scn8admu/+ mice demonstrated improved motor capacity during the recovery and early chronic phases of EAE relative to wild-type animals. In the optic nerve, myeloid cell infiltration and the effects of EAE on the axonal ultrastructure were also significantly reduced in Scn8admu/+ mice. Analysis of innate immune parameters revealed reduced plasma IL-6 levels and decreased percentages of Gr-1high/CD11b+ and Gr-1int/CD11b+ myeloid cells in the blood during the chronic phase of EAE in Scn8admu/+ mice. Elevated levels of the anti-inflammatory cytokines IL-10, IL-13, and TGF-β1 were also observed in the brains of untreated Scn8admu/+ mice. A lipopolysaccharide (LPS) model was used to further evaluate inflammatory responses. Scn8admu/+ mice displayed reduced inflammation in response to LPS challenge. To further evaluate if this was an immune cell-intrinsic difference or the result of changes in the immune or hormonal environment, mast cells were derived from the bone marrow of Scn8admu/+ mice. These mast cells also produced lower levels of IL-6, in response to LPS, compared with those from wild type mice. Our results demonstrate that in addition to its recognized impact on axonal damage, Nav1.6 impacts multiple aspects of the innate inflammatory response.